Increasing prevalence of diabetes in Bangladesh: a scoping review. (September 2016) - Biswas, T.; Islam, A.; Rawal, L.B.; Islam, S.M.S.
Abstract: Background: The prevalence of type 2 diabetes is increasing rapidly in Bangladesh. However, studies documenting the increasing trend of diabetes prevalence are scarce. The aim of this study was to conduct a scoping review of published literature to ascertain the changing patterns of diabetes prevalence in Bangladesh. Methodology: We conducted a scoping review based on York scoping reviews framework and performed a comprehensive search of published literature through Medline, BanglaJOL, and Google Scholar published between 1994 and 2013. We summarised and calculated the time trends and pooled prevalence for type 2 diabetes among adults (≥18 years) in both urban and rural areas in Bangladesh. Results: Of 152 studies identified, we included 22 studies for the scoping review which met the inclusion criteria. Overall, 11 studies (50%) were conducted in rural areas, eight in urban (36%) and three (14%) in semi-urban, semi-rural and tribal areas. The overall prevalence of type 2 diabetes ranged between 4.5% and 35.0%. The final estimate of diabetes prevalence obtained after pooling of data from individual studies among 51, 252 participants was 7.4% (95% CI 7.2–7.7%). The prevalence of diabetes was higher in males compared to females in urban areas and vice-versa in rural areas. Analyses of exponential trend revealed an increasing trend of diabetes prevalence among urban and rural population at a rate of 0.05% (R = 0.18) and 0.06% (R = 0.35) per year, respectively. Conclusion: The prevalence of type 2 diabetes showed an increasing trend in both urban and rural population in Bangladesh. Our findings suggest the need for an all-out effort by the government and stakeholders to implement preventive strategies for diabetes in Bangladesh. Highlights: The prevalence of type 2 diabetes in Bangladesh ranged between 4.5% and 35%. The overall pooled prevalence was 7.4% (95% CI 7.17%–7.63%). Type 2 diabetes showed an increasing trend in both urban and rural population in Bangladesh.